Check the checks: a comparison of fact-checking practices between newspapers and independent organizations in the United States - Diep, Pham Phuong Uyen (Kansas State University, 2022)
By conducting content analyses of 440 fact checks (N = 440), the study examined the fact-checking practices of three leading national newspapers (i.e., The New York Times, The Washington Post, and USA Today) and three independent fact-checking organizations (i.e., FactCheck.org, PolitiFact, and Snopes.com) in the United States during the 2020 presidential debates and town halls. The results found differences in how two types of organizations fact-check in terms of candidates, ratings, used sources, and topics. H1 and H2 were supported and partially supported, respectively, suggesting that three news organizations fact-checked Trump’s statements more than Biden’s, compared to three independent organizations. Fact-checking practices implications were further discussed in the context of polarization and truth decay.
Keywords: Fact-checking; Presidential debates; Newspapers